Water Balance Studies for Agricultural Planning in Udaipur Region - Jat, M L; Singh, Rajvir; Baliyan, J K; Kumpawat, B S (Annals of Arid Zone, 2016)
Based on the weekly water balance computations for Udaipur region (1981-1995), the variability in the mean length of growing season was analyzed. The date of commencement of kharif season rains was found to influence considerably, the period of water availability for crop growth (appropriate cropping plan). Based on the analysis cultural operation schedule is suggested. Water harvesting potential in the region is projected with different amounts.